Improving Students’ Learning Interest Through the Contextual Teaching and Learning (CTL) in Geometry - Junianto; Katon Agung Ramadhan; Aulia Fonda; Muh Wildanul Firdaus; Nur Hidayat Pamungkas (Mathematics Research and Education Journal, 2026)
Low student interest remains a persistent issue in mathematics education. This study investigated the effectiveness of the Contextual Teaching and Learning (CTL) approach in enhancing students’ interest in learning mathematics. The research involved all students from a public junior high school in Yogyakarta, Indonesia. Using a quasi-experimental design, two eighth-grade classes were selected as the experimental and control groups, with 34 students in each class. Data were collected through a learning-interest questionnaire and classroom observations. The questionnaire employed a Likert scale and was administered before and after the treatment. Instrument validity was examined using the Pearson Product Moment correlation, while reliability was tested through Cronbach’s Alpha. The findings indicated that CTL significantly improved students’ learning interest compared with the conventional expository approach. Students in the experimental class showed greater enthusiasm, participation, and engagement during mathematics lessons because the learning activities were connected to real-life situations and meaningful experiences. Statistical analysis using a one-sample t-test and an independent-sample t-test at a 5% significance level confirmed that the increase in learning interest among students taught through CTL was significantly higher than that of students taught through expository instruction.